The catholic kingdom of Ethiopia: father Manuel de Almeida’s account of the imperial conversion ceremony - Cohen, Leonardo (2014)
This article analyzes the detailed account of the conversion ceremony of Emperor Sus nyos to Catholicism, as it was compiled by Father Manuel de Almeida in his book "História da Etiópia". At this ceremony, Afonso Mendes, the recently appointed Patriarch of Ethiopia, gave a learned exposition on Church history that championed the authority of Rome above all else. Father Mendes’ speech reveals, beyond all doubt, that he was more interested in expounding upon ecclesiastical history and the various heresies that had shaped the Church’s past than contending with the premises and concerns of his Ethiopian hosts. From the Catholic patriarch’s standpoint, primitive heresy had inevitably tainted the Alexandrine Church. For Emperor Sus nyos, the proceedings on February 11, 1626 were indeed a confirmation ceremony, but they also gave rise to a new version of Ethiopian religious history. This article presents for the first time an English version of this account and the original text in Portuguese accompanied by an introduction and detailed notes.